PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KEPUASAN KERJA KARYAWAN DI PTPN V PEKANBARU - Conie Nopinda Br Sitepu (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2019)
ABSTRACT This is reseach done at PT. Perkebunan Nusantara V Pekanbaru at Rambutan street No. 43 Pekanbaru. The purpose of this research is to get to know whether the application of Total Quality Management (TQM) gives any influence to the level of employee’s satisfaction at PT. Pekebunan Nusantara V Pekanbaru either simultan easly or parcially. The population this reseach the employee of PT. Perkebunan Nusantara V Pekanbaru which are 147 employees. This research used double linier regression analysis and from the data analyzis used quantitative method by SPSS (Services For Product and Statistic Solution). Based on the result of the research that simultaneosly appreciation and confession, teawork, and the organization culture influence simutaneously to the satisfaction of the employee’s work, that parcially appreciation and confession and organisation culture give the significant influence to the satisfaction of the employee’s work at PT Perkebunan Nusantara V while the teamwork didn’t give any significant influence. This research also got from that all (three) independent variables could explains the unity variable with the perfect relationship for 31,5 persen. Keywords : TQM, The Satisfaction of the Employee’s Work